Cross-Sectional and Longitudinal Association between Neighborhood Environment and Perceived Control in Older Adults: Findings from HRS - Lee, Sunwoo (International journal of environmental research and public health, 2021)
The current study examined how neighborhood environments are related to older adults' perceived control over time. A longitudinal study design was employed using data sampled from the Health and Retirement Study (HRS) 2014 and 2018. In total, 3170 older adults, whose age ranged between 60 and 99 years at the baseline, were followed up with a 4-year lag. Measures included two domains of neighborhood characteristics: social cohesion and physical disorder (at baseline and follow-up) and perceived control (at follow-up). Path coefficients between the latent factors were examined using structural equation modeling. Results showed that there was a significant cross-sectional and longitudinal association between neighborhood social cohesion and older adults' perceived control, while neighborhood physical disorder was cross-sectionally associated with perceived control. Study findings provide evidence for promoting social integration and social capital in their neighborhood that might contribute to older adults' perceived competence and beliefs in control.
Keywords: průřezové studie; důchod; sociální kapitál; Residence Characteristics; Cross-Sectional Studies; neighborhood characteristics; Longitudinal Studies; older adults; social cohesion; perceived control; longitudinální studie; neighborhood; Social Capital; charakteristiky bydlení; Retirement